A256 SURVEILLANCE OF SMALL, NON-FUNCTIONING, ASYMPTOMATIC PANCREATIC NEUROENDOCRINE TUMORS: THE BRITISH COLUMBIA EXPERIENCE. (21st February 2022) - Jiang, S X; Towfighi, S; Owen, D; Tomaszewski, M; Harris, A; Donnellan, F
Abstract: Background: Expert consensus surrounding surveillance for small, non-functioning, asymptomatic pancreatic neuroendocrine tumors (PNETs) remains conflicting. Recent observational studies have shown that surveillance is a safe strategy while large database studies show superior overall survival with surgical resection. Aims: To describe the growth of small (<2cm), non-functioning, asymptomatic PNETs undergoing surveillance at a tertiary hospital in British Columbia. Methods: We conducted a retrospective case series of patients with biopsy-proven, non-functioning, asymptomatic PNETs which were <2cm by RECIST criteria at diagnosis, who were followed through active surveillance at Vancouver General Hospital, British Columbia from February 1, 2011-February 1, 2021. Patients were included if serial imaging, whether by endoscopic ultrasound or cross-sectional imaging, was available for a minimum of 24 months. Results: Of the 57 patients with pathology-proven PNETs that were identified, 14 cases were included after excluding those with resection within 1 year (n=17), lost to follow up (n=13), metastatic disease (n=6), size greater than 2cm at diagnosis (n=4), and with concurrent cancer (n=3). Included patients were predominantly female (n=10, 71%), Caucasian (n=8, 57%), and had a mean Charlson comorbidity index of 3.14. Mean PNET size at diagnosis was 12mm with standard deviation of 4.26mm. Tumors were located in the pancreatic head (n=4, 29%), body (n=6, 42%), and tail (n=4, 29%). Of 8 patients who had Ki67 stains, all were <3%, and of 11 patients with mitotic index, all had <2 mitotic figures. As such, of the 8 patients with available WHO grading, all were grade 1. The average follow-up was 49.6 months with an average tumor growth of 0.82mm per year. When grouping these tumors by growth, 9 (62%) tumors exhibited no growth, 2 tumors grew <1mm per year, 2 tumors grew 1-1.5mm per year, and 1 tumor grew 7.7mm per year. Two cases (14%) of PNETs underwent surgical resection due to size surpassing 2 cm. No patients undergoing surveillance developed metastatic disease. Conclusions: To our knowledge, we have performed the first Canadian series of small, low-grade PNETS and demonstrated that active surveillance is a safe strategy with most tumors exhibiting no growth of several years. Of the subset of PNETs which demonstrate progression, the preceding surveillance strategy did not disadvantage patients in terms of progression to metastases and allowed for delay of potentially morbid surgery. Further research with prospective studies and larger samples should be conducted. Funding Agencies: CAG